Second hankel determinant of certain subclasses of analytic Bi-Univalent functions subordinate to chebyshev polynomials / Nadzira Amanina Mohamad, Noor Aleeza Abdul Wahab and Amy Aizaitul Aina Shuhaimee - Mohamad, Nadzira Amanina; Abdul Wahab, Noor Aleeza; Shuhaimee, Amy Aizaitul Aina (2018)
In geometric function theory, there are many types of class of analytic function that had already been introduced by many researchers. For every class of analytic function that have been defined and introduced, it has its own properties to be considered. However, the properties ob¬ tained are based on the suitability of the class of analytic functions.To determine the related properties of each class of analytic functions, extreme function must first be determined.